2016
DOI: 10.1016/j.ceramint.2016.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced afterglow properties of Nd3+ co-doped Sr2MgSi2O7: Eu2+, Dy3+ synthesized by sol–gel method

Abstract: In this study, Sr 1.94 MgSi 2 O 7 : 0.02Eu 2+ , 0.04Dy 3+ and Sr 1.928 MgSi 2 O 7 : 0.02Eu 2+ , 0.04Dy 3+ , 0.012Nd 3+ long afterglow luminescent materials were successfully synthesized via the sol-gel method under reducing atmosphere at 1100 o C for 3 h. No phase structure effect of Sr 2 MgSi 2 O 7 , or significant lattice distortion occurred while a small amount of rare earth ions were doped. Moreover, co-doping Sr 2 MgSi 2 O 7 : Eu 2+ , Dy 3+ with Nd 3+ has virtually no effect on the morphology of Sr 2 MgSi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The reliability parameters are Rwp = 9.62%, Rp = 7.41%, and χ 2 = 1.757, which illustrate the reliability of the refinement results. The refinement results confirmed that SrBaZn 2 Ga 2 O 7 crystallized in the isomorphic hexagonal phase with the space group P63mc, and the cell parameters are a = b = 6.44962 (11) Å, c = 10.21639(20) Å, and V = 367.732(16) Å. Figure 1c shows the crystal structure, which consists of SrO 6 octahedra, BaO 12 polyhedra, and (Ga/Zn)O 4 tetrahedra.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…The reliability parameters are Rwp = 9.62%, Rp = 7.41%, and χ 2 = 1.757, which illustrate the reliability of the refinement results. The refinement results confirmed that SrBaZn 2 Ga 2 O 7 crystallized in the isomorphic hexagonal phase with the space group P63mc, and the cell parameters are a = b = 6.44962 (11) Å, c = 10.21639(20) Å, and V = 367.732(16) Å. Figure 1c shows the crystal structure, which consists of SrO 6 octahedra, BaO 12 polyhedra, and (Ga/Zn)O 4 tetrahedra.…”
Section: Resultsmentioning
confidence: 61%
“…1−4 As a special energy-storage luminescence material, it has been widely used in architectural decoration, information display, and security indication and now gradually extended to the application fields of information anticounterfeiting, biological detection, and optical imaging. 5−8 To date, blue-green PersL materials have been reported extensively, mainly focusing on aluminate and silicate systems, such as SrAl 2 O 4 :Eu 2+ ,Dy 3+ (520 nm), 9 CaAl 2 O 4 :Eu 2+ ,Nd 3+ (450 nm), 10 and Sr 2 MgSi 2 O 7 :Eu 2+ ,Dy 3+ (470 nm), 11 which have excellent PersL properties and have been commercially produced. However, the development of warm-color PersL materials is relatively backward and only the orange PersL material Y 2 O 2 S:Eu 3+ ,Mg 2+ ,Ti 4+ can meet the commercial requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The defects V O , V Sr 0 , Eu Sr , and Dy Sr Á were produced during the solid-state reaction. The grain surface is the defect aggregation surface that acts as the shallow traps, and the isolated traps in the materials act as the deep traps [44]. When the material was excited, more electrons and holes were generated, transferred, captured by traps and finally released, so the afterglow curve could be fitted effectively by the three-exponential equation [45][46][47][48].…”
Section: The Luminescence Mechanism Of the Rod-like Long Afterglow Ma...mentioning
confidence: 99%
“…Rare-earth-ion doping is known to increase lattice defects that are already present in the crystal. Thermoluminescence curves [44] indicate that, around 100 °C, post-luminescence properties increase due to deeper traps. Other studies [45] show that, at 80 °C, the curves show a strong thermoluminescence peak with much wider bands.…”
Section: Optical Propertiesmentioning
confidence: 99%